2020
DOI: 10.2478/jlecol-2020-0018
|View full text |Cite
|
Sign up to set email alerts
|

Forest Transformation Urgency for Topsoil Diversity Optimization During Environmental Change

Abstract: Combined effect of environmental change and management variability leads to reduced soil diversity in homogenous forest stands. On the other hand, forest soil diversity is maintained with rich tree species composition. In this study, focus has been put on deriving urgency to change forest tree species composition in order to increase soil diversity in biogeographic regions with uneven impact of environmental change. The relation of forest tree species and soil diversities was compared between the periods of do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 55 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…The univariate analysis and the box plots clearly show that the total microbial activity, measured by fluorescein diacetate assays, is significantly higher near the surface in the topsoil region. Recent studies also confirmed this heterogeneity regarding the microbial biomass and diversity (Mukhtar et al, 2021;Samec et al, 2020). It was stated that the microbial abundance and the structure of the community are decreasing with depth in a vertical soil profile.…”
Section: Relationship Between Fda Microbial Activity and Pte Distribu...mentioning
confidence: 74%
“…The univariate analysis and the box plots clearly show that the total microbial activity, measured by fluorescein diacetate assays, is significantly higher near the surface in the topsoil region. Recent studies also confirmed this heterogeneity regarding the microbial biomass and diversity (Mukhtar et al, 2021;Samec et al, 2020). It was stated that the microbial abundance and the structure of the community are decreasing with depth in a vertical soil profile.…”
Section: Relationship Between Fda Microbial Activity and Pte Distribu...mentioning
confidence: 74%
“…The spatial dependence of forest-plant diversity on soil diversity indicates the integrity of the community with the bedrock. The correlations of the Central European forest diversity suggest distribution of their response to the variability of growth conditions along a gradient of soils with different fertility [49]. Soils of bedrock-derived fertility are less diversified and display lower resistance to changes in other environmental properties.…”
Section: Discussionmentioning
confidence: 99%
“…Physico-chemical properties were characterized by pH, determined by acidometry and by sorption properties: cation exchange capacity (CEC) and base saturation (BS) determined by ion-selective extraction. Substance budget determination addressed C org , N tot , Al 2 O 3 , CaO, MgO a P 2 O 5 , which are together with physical and physico-chemical soil properties most significantly differentiated in the Czech Republic [49].…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation